In vitro diagnostic assays are effective during the acute phase of delayed‐type drug hypersensitivity reactions. (31st January 2013) - Polak, M.E.; Belgi, G.; McGuire, C.; Pickard, C.; Healy, E.; Friedmann, P.S.; Ardern‐Jones, M.R.
Summary Background Previous reports have suggested that drug‐specific lymphocyte proliferation assays (LPA) can be used retrospectively to confirm the culprit drug following delayed‐type drug hypersensitivity reactions (DHR). However, only limited evidence supports their use in aiding acute clinical management. The aim of this study was to compare the LPA against combination cytokine assays for potential use in the acute setting. Methods A total of 43 patients with DHR (19 during the acute reaction, 20 after recovery, four during acute and after recovery) and 14 control subjects without DHR were investigated using ex vivo analysis of drug‐specific proliferation, and interferon (IFN)‐γ and interleukin (IL)‐4 production. Results Healthy controls showed negative drug‐specific proliferation and cytokine release in contrast to individuals with a known sensitivity (P < 0·0001). The assays demonstrated a test specificity of 95% (LPA), 83% (IFN‐γ) and 92% (IL‐4). The sensitivity of combined measurement of drug‐specific IFN‐γ and IL‐4 cytokines during acute DHR was better than LPA (82% vs. 50%), but all assays were less sensitive during the recovery phase. The correlation between LPA and IFN‐γ assays was strong (r = 0·7, P < 0·0001), whereas the IL‐4 assay did not correlate as well with either of these assays. In contrast to LPA, drug enzyme‐linked immunosorbent spot assays showed positive responses in patients concurrently taking immunosuppressive medication. Conclusions In vitro assays of drug‐specific IFN‐γ and IL‐4 production offer potential for use as rapid diagnostic tests. Cytokine detection offers distinct advantages over the LPA, including a shorter assay time, a greater sensitivity and effectiveness in testing immunosuppressed patients.